2003
DOI: 10.1210/jc.2002-020510
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of 11β-Hydroxysteroid Dehydrogenase Type 1 in Mature Human Subcutaneous Adipocytes by Hypothalamic Messengers

Abstract: Glucocorticoids are regulated at the prereceptor level by 11 beta-hydroxysteroid dehydrogenase (11 beta-HSD), which interconverts inactive cortisone and active cortisol. In a previous study, we noted that patients with hypothalamic obesity had an increased ratio of cortisol/cortisone metabolites, suggesting enhanced 11 beta-HSD-1 activity. In this in vitro study, we tested the hypothesis that adipose 11 beta-HSD-1 is regulated by the hypothalamus via circulating hormones, sympathetic nervous system innervation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
53
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 77 publications
3
53
0
Order By: Relevance
“…All proinflammatory cytokines tested increased DHC-induced apoptosis, suggesting an increase in expression levels and reductase activity of 11␤-HSD1. Later effects have been observed in a rat embryonic cell line (10) and in adipocytes (14). Consequently, in an inflammatory condition associated with severe stress, the GC action can be amplified at the cellular level by an increase of 11␤-HSD1 expression or activity under the influence of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…All proinflammatory cytokines tested increased DHC-induced apoptosis, suggesting an increase in expression levels and reductase activity of 11␤-HSD1. Later effects have been observed in a rat embryonic cell line (10) and in adipocytes (14). Consequently, in an inflammatory condition associated with severe stress, the GC action can be amplified at the cellular level by an increase of 11␤-HSD1 expression or activity under the influence of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 98%
“…36 Finally, we reported that in SAT, TNFa expression increased in parallel with 11b-HSD1 expression and this is in keeping with the evidence that TNFa increases 11b-HSD1 transcription in human adipose tissue. 37,38 The hypothesized decrease in adiponectin release would contribute to increase TNFa mRNA levels due to the hampering effect of this protein on TNFa transcription. 39 In conclusion, our study showed that in obese subjects, increased 11b-HSD1 expression in SAT, but not in VAT, is associated with the worsening of metabolic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Among other regulatory mechanisms of enzyme activity (27), GH inhibits 11␤-HSD-1 activity and gene expression, while GH deficiency is associated with enhanced enzyme activity (28 -31).…”
mentioning
confidence: 99%